The Effect of Governance Principles on Functional Performance: An Empirical Study on East Nasr City - Alwakeel, Manal (The Arab Journal of Administration, 2021)
The present study aims to explore the relationship of governance principles to job performance in East Nasr City and to identify the relationship and the impact of leadership adoption of governance as an intermediate variable for the relationship between the principles of governance and improving job performance. Three main hypotheses of the research were tested: There is no statistically significant impact between the application of governance principles and improving job performance in East Nasr City district, There is no statistically significant impact between administrative leaders and the application of governance principles, There is no statistically significant impact between the adoption of administrative leaders to apply the principles of governance and improve job performance in East Nasr City. The study relied on the use of the descriptive analytical method, and the use of a measurement tool developed to conform with the objectives of the study and its hypotheses in terms of investigating the relationship and the impact of governance principles and the adoption of leadership on the performance and improve performance. The results showed that there is a correlation with a statistically significant correlation which is a positive correlation between the application of the principles of governance and improving the functional performance in East Nasr City where the value of the correlation coefficient (r 0.865), the existence of a correlation with a statistically significant correlation is a direct relationship between the administrative leaders and the application of the principles of governance where the value of the correlation coefficient (r 0.744), t was also found that there is a correlation with a statistically significant significance, which is a direct relationship between the adoption of administrative leaders to apply the principles of governance and improve job performance where the value of the correlation coefficient (r 0.861). The results confirmed that governance contributes positively to improving the institutional performance of the administrative bodies. The study recommended the introduction of principles of governance and activation in public organizations and through the roles of leaders towards adopting the foundations and standards of discipline, transparency, independence, accountability for responsibility, responsibility, justice, social awareness.